Assessment of heavy metals and proximate composition in poultry feed: a study from Dhaka and Rangpur, Bangladesh: Assessment of heavy metals and proximate composition in poultry feed - Tabassum, Anika; Hassan, Mohammad Tariqul; Hasan, Md Mahfujul; Islam, Shiek Muzahidul; Begum, Maksuda (Bangladesh Journal of Scientific and Industrial Research, 2025)
The study investigates the contamination concentrations of heavy metals lead (Pb), cadmium (Cd), and chromium (Cr) in commercial poultry feeds in Bangladesh and evaluates their proximate composition. Using atomic Absorption Spectrophotometry for heavy metal analysis and standard methods for proximate composition, the study analyzed 50 poultry feed samples. Results revealed significant heavy metal contamination in a substantial number of samples, with Pb (≤4.65 mg/kg), Cd (≤0.398 mg/kg), and Cr (≤16.13 mg/kg) levels exceeding permissible limits set by regulatory bodies. This contamination poses serious health risks to poultry and humans, highlighting the potential for bioaccumulation and subsequent entry into the human food chain. Furthermore, the proximate composition analysis showed considerable variability in nutrient profiles among different feed brands, raising concerns about the adequacy of nutritional quality. The findings emphasize the urgent need for firm regional regulation and regular monitoring of poultry feed quality in Bangladesh to ensure public health safety and enhance poultry production sustainability. Implementing comprehensive quality control measures will protect consumer health and support the growth and profitability of the poultry industry in the country. Bangladesh J. Sci. Ind. Res. 60(4), 263-274, 2025